Canadian missionaries, indigenous peoples : representing religion at home and abroad - Austin, Alvyn, 1945-; Scott, Jamie S. (CEL - Canadian Publishers Collection., 2005)
Christian missions and missionaries have had a distinctive role in Canada's cultural history. With Canadian Missionaries, Indigenous Peoples, Alvyn Austin and Jamie S. Scott have brought together new and established Canadian scholars to examine the encounters between Christian (Roman Catholic and Protestant) missionaries and the indigenous peoples with whom they worked in nineteenth- and twentieth-century domestic and overseas missions. This tightly integrated collection is divided into three sections. The first contains essays on missionaries and converts in western Canada and in the arctic. The essays in the second section investigate various facets of the Canadian missionary presence and its legacy in east Asia, India, and Africa. The third section examines the motives and methods of missionaries as important contributors to Canadian museum holdings of artefacts from Huronia, Kahnawaga, and Alaska, as well as China and the South Pacific. Broadly adopting a postcolonial perspective, Canadian Missionaries, Indigenous Peoples contributes greatly to the understanding of missionaries not only as purveyors of western religious values, but also as vehicles for cultural exchange between Native and non-Native Canadians, as well as between Canadians and the indigenous peoples of other countries.